Рассказы - Житков Борис Степанович (Школьная библиотека, 2021)
Экземпляры: (20220218) / Инвентарный номер: 42014 / Цена: 95.00 / Сис.шифр: 84(2=411.2)6 / Авт.знак: Ж 74 / ГРНТИ: 17.82.93 / ББК: 84(2=411.2)6